Customer style inventory, the usage of Facebook, and purchase intention: are they connected? - Widarto Rachbini; Anna Agustina (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2019)
This study investigates the influence of price, brand, and novelty consciousness of customer style inventory (CSI) on purchase intention of shoes using Facebook. The involvement of opinion seeking using electronic word of mouth (eWOM) and attitude towards social online shopping as mediators of relationship between CSI and purchase intention is also tested. Purposive sampling method was employed, and respondents mainly are residents of the city of Jakarta and Bekasi. The study reveals that brand, price and novelty consciousness influence the opinions seeking through eWOM and attitudes towards online social shopping, which ultimately influence purchase intention of shoes product via Facebook. However, brand consciousness of shoes only plays small role on opinions seeking. Individual with brand consciousness of shoes reduces opinion seeking through eWOM in Facebook. While, price and novelty of shoes might become point of attention while consumers using Facebook.